Pancake bouncing of impacting nanodroplets on smooth and nanopillared surfaces - Ma, Qiang (2024)
Reducing the contact time of impacting droplets on solid surfaces has become a research focus due to its promising application prospects in self-cleaning, anti-erosion, and anti-icing. In this study, the pancake bouncing of nanodroplets is investigated through molecular dynamics simulations, achieving a remarkable reduction in contact time. Two distinct patterns of pancake bouncing are identified when nanodroplets impact smooth and nanopillared surfaces with different bouncing mechanisms. The first pancake bouncing pattern with holes on smooth surfaces is attributed to internal-flow collision induced by multiple retraction centers. The second pancake bouncing pattern on nanopillared surfaces results from the storage and release of sufficient surface energy due to liquid penetration and requires satisfying both the timescale and energy criterion. Subsequently, theoretical models for two criteria are developed, which promote two parameter groups (−(s2 + 2ws)h(wcosθ0)−1 and We–1/3Re–1/3R02) corresponding to the surface and droplet. Based on these two parameter groups, a phase diagram is established and indicates the triggering conditions for the second pancake bouncing patterns. Finally, it is further revealed that by increasing the pillar height from smooth to nanopillared surfaces, the bouncing regime is transformed from the first pancake bouncing pattern, regular bouncing, to the second pancake bouncing pattern.